2018
DOI: 10.1111/1755-5922.12440
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and consequences of postdischarge gastrointestinal bleeding after percutaneous coronary intervention

Abstract: In this large cohort of real-world patients after PCI, postdischarge GIB was not significantly associated with MACCE up to 2 years of follow-up but lead to an increase in DAPT cessation, and DAPT cessation was strongly associated with 2-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ 23 ] High-dose or multi-drug combined anticoagulation may cause acute gastrointestinal bleeding after PCI. Zhu et al [ 24 ] indicated that renal dysfunction was an independent risk factor of post-discharge 1-year GIB after PCI. Similarly, Gaglia et al [ 25 ] found that variables associated with increased risk of GIB included older age, shock, acute myocardial infarction, chronic renal insufficiency, lower baseline hematocrit, and glycoprotein IIb/IIIa inhibitors in their study.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] High-dose or multi-drug combined anticoagulation may cause acute gastrointestinal bleeding after PCI. Zhu et al [ 24 ] indicated that renal dysfunction was an independent risk factor of post-discharge 1-year GIB after PCI. Similarly, Gaglia et al [ 25 ] found that variables associated with increased risk of GIB included older age, shock, acute myocardial infarction, chronic renal insufficiency, lower baseline hematocrit, and glycoprotein IIb/IIIa inhibitors in their study.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Primary PCI has been shown to be very successful in restoring the patency of coronary arteries after acute myocardial infarction and thus in this way salvaging the ischemic myocardium. 5,6 Acute gastrointestinal tract bleeding after the invasive coronary artery procedures has been extensively studied for its predictive risk factors and clinical impacts and these are well documented in the literature. 7,8 However little data is present for Post-graduate teaching hospitals, tertiary care hospitals and National cardiology Institutes in Pakistan.…”
Section: Introductionmentioning
confidence: 99%